Perbedaan Skala Analog Visual Nyeri dan Kadar Protein C-reaktif Sensitivitas Tinggi Setelah Pemberian Fentanil dan Ketamin Perioperatif pada Pasien Pasca-laparotomi: Sebuah Uji Klinis Terkontrol Acak Buta Ganda: Penelitian - Mahendra, Adiptya Cahya; Thamrin, Muhammad Husni; Putro, Bambang Novianto; Dzikri, Dykall Naf’an (PT Kalbe Farma Tbk., 2026)
Introduction: Postoperative pain remains a significant challenge in perioperative management. This study aims to analyze the differences in pain scores using the visual analog scale (VAS) and high-sensitivity C-reactive protein (hsCRP) levels between perioperative ketamine administration and perioperative fentanyl administration in post-laparotomy patients. Methods: A double-blind randomized controlled trial was conducted on 24 laparotomy patients divided into ketamine (n = 12) and fentanyl (n = 12) groups. The ketamine group received a 0.2 mg/kg bolus followed by a 0.1 mg/kg/hour infusion, while the fentanyl group received a 0.5 mcg/kg/hour infusion during surgery; drug administration was stopped immediately after extubation. VAS scores were assessed at 4 and 8 hours postoperatively, and hsCRP levels were measured preoperatively and 6 hours postoperatively. Statistical analysis used independent t-tests, Mann-Whitney U tests, and Pearson correlation. Results: The ketamine group showed significantly lower VAS scores at 4 hours postoperatively (2.92 vs 5.25; p = 0.017), but no significant difference at 8 hours (6.00 vs 5.75; p = 0.514). Postoperative hsCRP levels were lower in the ketamine group compared to fentanyl (4.58 vs 7.77; p = 0.006). A positive correlation was found between increased VAS scores and elevated hsCRP (r = 0.566; p = 0.004). Conclusion: Ketamine provides significantly superior early postoperative analgesia and more effectively suppresses the acute inflammatory response than fentanyl. However, its analgesic advantage diminishes by 8 hours, indicating the need for a multimodal strategy for sustained postoperative pain management.